Functional divergence of the RNA polymerase II transcription machinery in Plasmodium falciparum - Knopp, Jasmin (Department of Molecular and Cell Biology, 2025)
This thesis describes the functional characterisation of three Plasmodium falciparum general transcription factors - two TBP family proteins designated the TATA-binding protein (TBP) and TBP like protein (TLP), and the P. falciparum orthologue of general transcription factor IIB (TFIIB). Through the biochemical characterisation of protein-DNA interactions, protein-protein interactions and the biomolecular condensation properties of these transcription factors, this study aimed to provide insight into the molecular mechanisms governing promoter recognition and the regulated assembly of the RNA polymerase II transcription initiation complex in P. falciparum, which are hitherto not understood. The work shows that P. falciparum expresses two highly divergent TBP family proteins that do not possess sequence-specific TATA box-binding activity. Both PfTBP and PfTLP bind DNA with a general preference for A/T-rich sequences, mediated through interactions with the DNA minor groove, without detectable preference for specific sequence motifs. PfTBP and PfTLP are thus unlikely to contribute to the recognition of specific promoter regions within the A/T-rich context of the P. falciparum genome. The study further characterises TBP-independent DNA-binding of PfTFIIB, a Plasmodium-specific feature not seen with TFIIB in well-studied eukaryotes. The data presented here show that PfTFIIB binds to DNA in an unspecific manner. Interestingly, PfTFIIB stimulates the DNA binding activity of PfTBP and PfTLP and forms stable PfTBP-PfTFIIB-DNA and PfTLP-PfTFIIB-DNA nucleoprotein complexes. However, these PfTFIIB interactions do not detectably enhance the sequence-selectivity of PfTBP- or PfTLP-DNA interactions. Thus, recognition of genomic regions at which transcription is preferentially initiated must involve additional factors or may depend to a lesser extent on the recognition of specific core promoter elements by the general transcription machinery. Transcription condensates play an important role in eukaryotic transcription regulation. In this study, the potential role of PfTFIIB in the formation and regulation of P. falciparum transcription condensates is investigated by fluorescence microscopy using a panel of fluorescent protein-tagged PfTFIIB fusion proteins. The work demonstrates that PfTFIIB undergoes condensation at nanomolar concentrations, and partitions with PfTBP and PfTLP into mixed phase separated condensates. Furthermore, assembly and properties of PfTFIIB condensates are shown to be strongly influenced by the presence of DNA and RNA. Interestingly, PfTBP and PfTLP are found to localise in discrete foci in cultured P. falciparum blood-stage parasites. Together, these results provide first evidence for the existence of transcription condensates, mediated by transient multivalent interactions between general transcription factors, in the P. falciparum malaria parasite.